Correlation between Traditional Chinese Medicine Constitution and Dyslipidemia: A Systematic Review and Meta-Analysis. (22nd October 2017) - Ma, Ye-lin; Yao, Hui; Yang, Wei-jia; Ren, Xuan-xuan; Teng, Long; Yang, Min-chun
Abstract : Objective . To study the correlation between Traditional Chinese Medicine (TCM) constitution and dyslipidemia. Methods . CNKI, VIP, Wanfang database, CBMdisc, PubMed, and Embase were searched, and meta-analysis was performed by Review Manager 5.2 software. Results . Altogether 11 studies were included with 12890 individuals. The results showed that balanced constitution was a protective factor of dyslipidemia (OR = 0.62, 95% CI 0.47 0.82) while phlegm-dampness constitution was a risk factor of it (OR = 2.50, 95% CI 2.22 2.80), and the effect of phlegm-dampness constitution in South China (OR = 3.31, 95% CI 1.71 6.43) was more obvious than that in East (OR = 2.40, 95% CI 2.06 2.80) and North China (OR = 2.24, 95% CI 1.81 2.78). Conclusion . This study provides evidence for the prevention and treatment of dyslipidemia in TCM. However, most of the studies included are of moderate quality; more high quality, multicenter, large-sample studies are expected to provide higher level evidence.